2007
DOI: 10.1016/j.ijrobp.2006.12.016
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Early and Late Lung Sequelae After Conformal Radiotherapy in Breast Cancer Patients

Abstract: Our analyses indicate that the risks of early and late radiogenic lung sequelae are strongly related to the age of the patient, the volume of the irradiated lung, and the dose to it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
90
1
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(106 citation statements)
references
References 37 publications
9
90
1
4
Order By: Relevance
“…Moonkyoo Kong*, Seong Eon Hong (Halverson et al, 1993;Kahan et al, 2007), the role of supraclavicular nodal RT for N1 breast cancer patients is controversial, and it's use varies greatly between clinicians (Ceilley et al, 2005). A few studies have reported a subgroup of N1 breast cancer patients who may be at particularly high risk of SCLR and might benefit from supraclavicular nodal RT (Chen et al, 2002;Grills et al, 2003;Reddy and Kiel, 2007;Truong et al, 2009;Yu et al, 2010).…”
Section: Predictive Factors For Supraclavicular Lymph Node Recurrencementioning
confidence: 99%
“…Moonkyoo Kong*, Seong Eon Hong (Halverson et al, 1993;Kahan et al, 2007), the role of supraclavicular nodal RT for N1 breast cancer patients is controversial, and it's use varies greatly between clinicians (Ceilley et al, 2005). A few studies have reported a subgroup of N1 breast cancer patients who may be at particularly high risk of SCLR and might benefit from supraclavicular nodal RT (Chen et al, 2002;Grills et al, 2003;Reddy and Kiel, 2007;Truong et al, 2009;Yu et al, 2010).…”
Section: Predictive Factors For Supraclavicular Lymph Node Recurrencementioning
confidence: 99%
“…Some studies have reported a correlation between elevated serum TGF-β1 levels and increased fibrosis in breast cancer patients [18]. However, others have not found such associations [19]. Several small studies have reported a correlation between SNPs in the TGFB1 gene and fibrosis, one form of late radiotherapy toxicity, in breast cancer patients [20][21][22].…”
mentioning
confidence: 99%
“…Even though the values of capacities, volumes and respiratory muscle strength are within normality for the studied sample, and considering the spirometry as an important indicator of risk for the development of pulmonary diseases 18 , the reduction of the assessed parameters confirms the potentially negative effect caused by RT, in the short term, on the pulmonary functional reserve 6 . It is clear that these results should be considered important, since the life expectancy of women with breast cancer has increased, they have been adopting a more active life style, and due to the fact that this sample represents different women who, in the same age group, one day can be submitted to RT.…”
Section: Discussionmentioning
confidence: 70%
“…Besides, no significant correlation between pulmonary function and total radiation dose was found, which is in accordance with the profile of the studied patient 23 . Imaging tests can also be useful 5,6,12 , because at an acute phase, radiation can lead to the appearance of attenuation or consolidation areas in lung x-rays, while at a late stage, bronchiectasis areas and loss of volume can be observed 10,12 . However, it was not possible to demonstrate radiological changes in this study, because only tests of pulmonary function and fatigue assessment were conducted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation